Intracavity loss control effect on tuning range of tunable dual erbium-doped fiber laser - Abdullah F.; Noor A.S.M.; Mahdi M.A.; Rashid H.A.A.; Abdullah M.K. (2023)
This letter presents the effect of intracavity loss control on the tuning range of erbium-doped fiber laser (EDFL). The intracavity loss is controlled using a variable attenuator fitted inside the laser's cavity. The tuning range of uncontrolled cavity loss is around 3 nm, while the controlled cavity loss tuning range is 30 nm. 2005 by Astro Ltd.